Administrative Reform in Malaysia: Strategies for Promoting Efficiency and Productivity in the Public Service, 1981-1991 - Hussain, Ahmad Atory (Universiti Putra Malaysia Press, 1995)
This article is a macro-analysis of reform in the Malaysian civil service, covering the ten-year period between 1981 and 1991. These reforms were dictated by the need to increase efficiency, effeclivcness and productivity in order to speed up the implementation of development policies and deliver the economic goods to lhe people. This article brings into focus the opinions of high-ranking civil servants about reforms initialed during this period. The article concludes that though more effort is still needed, especially in determining how close programmes and policies have come to achieving their target, bureaucratic reforms carried out in Malaysia between 198] and] 99] have generally been successful in changing attitudes of civil servanl.S towards lhe goals of efficiency, effectiveness and productivity.